2017
DOI: 10.21010/ajtcam.v14i4s.8
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Patients With Metabolic Syndrome Is Improved After Whole Body Vibration Exercises

Abstract: Background:Whole body vibration exercises (WBVE) improve the quality of life (QoL) of different populations. Metabolic syndrome patients (MetS) may be favored by physical activity. Questionnaires are used to assess the QoL. The aim was to evaluate the QoL of patients with MetS that have undergone WBVE with a brief WHOQOL (WHOQOL-BREF).Material and Methods:MetS patients were randomly divided into three groups: (i) control group (CG), (ii) treated with WBVE once per week (WBVE1) and (iii) treated with WBVE twice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 31 publications
1
44
0
Order By: Relevance
“…The effects of WBV training on quality of life and foot health in people with T2DM have been poorly studied. Regarding quality of life, previous studies showed that WBV could improve the quality of life in older populations [45] and other chronic conditions [46,47]. In this regard, a previous study of 6 weeks of WBV improved all domains (pain, general and mental health, vitality, physical, emotional, and social functioning) of the SF-36 quality of life questionnaire in people with diabetic neuropathy.…”
Section: Discussionmentioning
confidence: 93%
“…The effects of WBV training on quality of life and foot health in people with T2DM have been poorly studied. Regarding quality of life, previous studies showed that WBV could improve the quality of life in older populations [45] and other chronic conditions [46,47]. In this regard, a previous study of 6 weeks of WBV improved all domains (pain, general and mental health, vitality, physical, emotional, and social functioning) of the SF-36 quality of life questionnaire in people with diabetic neuropathy.…”
Section: Discussionmentioning
confidence: 93%
“…One possible explanation to these discrepancies is related to differences in the intervention variables. Recent studies focused on the effects of WBVE intervention on daily physical functions in KOA individuals [45] used higher frequencies (35)(36)(37)(38)(39)(40) than the ones used in the current study. Moreover, Bokaeian et al, also reported improvements in symptoms of osteoarthritis of the knee and functionality; however, no significant differences were in pain or quality of life using a frequency of 25-30 Hz [22].…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was determined using the formula n = [(Zα/2δ)/E] 2 , where, n = sample size; Zα/2-critical value for the degree of confidence, usually: 1.96 (95%); δ-population standard deviation of the variable; E-standard error, usually: ±5% of proportion of cases (absolute precision) or ±5% of the mean [37]. Ten individuals were thus chosen for each group, considering the values (mean ± SD) reported in a previous study that assessed the QoL of individuals with osteoarthritis [38]. Considering a possible decrease in sample size, one hundred and three subjects with KOA diagnosis were recruited (January 2014 to December 2017).…”
Section: Sample Sizementioning
confidence: 99%
“…19 Different questionnaire form used to evaluate the quality of life, criteria to estimate MetS and sample size may cause variations in results in different studies. 20 We assessed MetS in our study by using hermonized criteria (H_MS). HRQL evaluated by using SF 36 questionnaire among the young adults in our study.…”
Section: Discussionmentioning
confidence: 99%